Practice of Critical Pedagogy in Higher Education Classrooms - Aryal, Shiva (AMC Journal, 2023)
Relying on the context of university teachers to unveils their awareness of and practice different tenets of critical pedagogy (CP). This article focuses on how university teachers perceive and practise diverse values of CP regarding classroom relationships, interactivity, and assignment-based learning in the constituent campuses of Nepal. The lived experiences elicited from the in-service’s teacher employing in-depth semi-structure interview within the frame of interpretative design have been interpreted in the article. In the context of prevailing classroom practices from the critical perspective, teacher holds the positive understanding towards using the critical pedagogy. Despite the importance of critical pedagogy, effectively, incorporating critical pedagogy in classroom pose the challenges related to teacher professionalism, collaboration, traditional mindset and administrative support as well as student-related issues. This paper suggests utilizing the critical pedagogy successfully; teacher requires to be more responsible, friendly, and professional.